Strategic Framework for Enhancing Organizational Efficiency and Innovation - Adiq Riyan Kurniawan (Arthatama: Journal of Business Management and Accounting, 2023)
The integration of Artificial Intelligence (AI) in knowledge management (KM) is transforming how organizations acquire, process, and utilize information. AI-driven systems enhance decision-making, streamline knowledge-sharing, and foster innovation by automating data analysis and optimizing information dissemination. This study explores the role of AI in KM, emphasizing its impact on organizational efficiency and competitive advantage. By leveraging machine learning, natural language processing, and predictive analytics, AI enables businesses to extract meaningful insights from vast data sources, improving strategic planning and operational effectiveness. However, challenges such as data privacy, ethical concerns, and technological adoption barriers remain critical. To address these issues, organizations must implement structured AI frameworks, invest in employee upskilling, and establish robust ethical guidelines. This study proposes a strategic model for AI-driven KM, providing insights into best practices and future research directions. Understanding AI’s potential in KM is essential for businesses seeking to enhance knowledge-based decision-making, improve efficiency, and maintain a sustainable competitive edge in the digital economy